Penerapan Pola Gerak Dominan Berbasis Video Tutorial Sebagai Media Terapi Fisik bagi ABK - Abdul Rachman Syam Tuasikal; Fransisca Januarumi Marhaendra Wijaya; Faridha Nurhayati; Kolektus Oky Ristanto; Mochamad Ridwan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to find out how to apply the dominant motion pattern based on video tutorials as a medium for physical therapy for children with special needs. The research method used is a survey with a questionnaire instrument. This study found that video tutorials as a medium for therapeutic at home for children with special needs in children aged 6-11 years get less significant results to do at home. The conclusion is the application of video tutorial-based dominant motion patterns as an ineffective physical therapy medium without particular companions. Keywords: Children with Special Needs, Video Tutorials, Physical Therapy, Companions.